Family of blind source separation methods based on generalised constant modulus criterion - Gu, N; Nahavandi, S; Yu, W; Creighton, D (Electronics letters, 2011)
In this paper, a family of blind source separation methods is presented, based on the extension of the generalised constant modulus criterion for MIMO systems. Different from other constant modulus based algorithms, which either employ the cross-correlation term or rely on the expensive Gram-Schmidt orthogonalisation technique to separate the sources successively, the proposed method utilises the Hadamard's inequality to retrieve signals. The main advantage of the proposed method is that the separation matrix can be updated simultaneously with a lower computational complexity. Hence, the propagation of estimation error due to successive source extraction can be prevented. The numerical simulations demonstrate the superior performance of the proposed algorithm.